COMPONENTS OF PEDAGOGICAL TECHNOLOGY FORMING THE PROFESSIONAL REFLEXION OF FUTURE SOCIAL PEDAGOGES IN THE HIGHER EDUCATIONAL INSTITUTION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
In the article the characteristics and peculiarities of pedagogical technology of formation of professional reflection of future social educators in the higher educational institution is a clear scientific and theoretical basis for the optimal realization of the tasks of vocational training. The developed pedagogical technology was considered as a collection of regular, functionally related components, constituting a definite integral system. The allocation of components in pedagogical technology has allowed it to be divided into blocks (target, functional, informative, organizational, productive) that provided the opportunity to more clearly represent the purposeful process of forming professional reflection of future social educators in the higher educational institution. The formation of a professional reflection of future social educators in a higher educational institution will be successful in the presence of appropriate pedagogical conditions. Moreover, it is necessary to identify, analyze and generalize in a systematic way those pedagogical conditions, to effectively influence this process and the professional formation of future social educators.The introduction of pedagogical technology for the formation of professional reflection of future social educators in a higher educational establishment is impossible without taking into account the pedagogical conditions for its implementation. In spite of the fact that they acted as part of the organizational unit of sound and developed pedagogical technology, in essence they were a kind of "core" that allowed it to function and be effective.
Keywords: pedagogical technology, professional reflection, social pedagogue, higher educational institution, pedagogical conditions.